Succession of Regional Heads Based on Kinship Relations Judging Concept of the Pancasila Legal State - Muslikhah, Umi; Chaidir, Ellydar; Sundari, Rini Irianty (Magister Hukum Universitas Semarang, 2024)
This research aims to examine in depth the existence of succession for Regional Heads using kinship relations in terms of the concept of the rule of law and formulate the implications of succession for Regional Heads based on kinship relations for the implementation of government duties in the region in the context of the rule of law. Indonesia, as stated in its constitution, adheres to the concept of a rule of law, this is attached to Article 1 paragraph (3) of the 1945 Constitution